EFL Students’ Perceptions of Online Learning using Zoom During Covid-19 Pandemic: A Case Study - Purwati, Diana; Khairunisa, Khairunisa (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2022)
Due to the Covid-19 pandemic, the transformation of learning has significantly switched from face-to-face learning to online learning. Many platforms have been utilized to support the teaching and learning process, one of them is the Zoom Meeting application. Although many studies have explored the educators’ and students’ perceptions of using Zoom, exploring the perspectives of EFL learners in the rural context remains a paucity. This study aims to explore the EFL students’ perspective using the Zoom Meeting application, particularly in the rural college context. This study employs a qualitative method. The data analysis is used thematic analysis. The results of this study show that the students have two sides perceptions of using Zoom; on the first side, EFL students thought that Zoom is very suitable to support online learning because the features available in the zoom meeting are varied and complete. However, on the other side, based on the students’ opinions, one of the negative sides of Zoom meetings is that this application tends to take up a lot of internet quota. This condition has forced the students to try to have free Wifi access in the public space and shared money to purchase the internet quota.